A Practical Update of Surgical Management of Merkel Cell Carcinoma of the Skin. (30th January 2013) - Tai, Patricia
Abstract : The role of surgeons in the treatment of Merkel cell carcinoma (MCC) of the skin is reviewed, with respect to diagnosis and treatment. Most of the data in the literature are case reports. Surgery is the mainstay of treatment. A wide local excision, with sentinel node (SLN) biopsy, is the recommended treatment of choice. If SLN is involved, nodal dissection should be performed; unless patient is unfit, then regional radiotherapy can be given. Surgeons should always refer patients for assessment of the need for adjuvant treatments. Adjuvant radiotherapy is well tolerated and effective to minimize recurrence. Adjuvant chemotherapy may be considered for selected node-positive patients, as per National Comprehensive Cancer Network guideline. Data are insufficient to assess whether adjuvant chemotherapy improves survival. Recurrent disease should be treated by complete surgical resection if possible, followed by radiotherapy and possibly chemotherapy. Generally results of multimodality treatment for recurrent disease are better than lesser treatments. Future research should focus on newer chemotherapy and molecular targeted agents in the adjuvant setting and for gross disease.